Risk factors of covid 19 transmission in cholera endemic countries - Atif Amin, Baig; Chandrika, Murugaiah; Constance, Liew Sat Lin (2020)
COVID-19 is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causing deaths, illnesses and economic despair. The least developed countries have limited or lack of medicine, ventilators, beds, water electricity, availability of doctors’ service for a large population and facing challenges to handle the economic fallout of the crisis. Cholera patients are more likely to reside in a slum, and this triggers worries with higher infection and spread chances if they were to be contracted with coronavirus. Decrease maternal education and reduce family income could increase cholera risk in rural children. Low Socioeconomic status, clean water supply and limited healthcare facilities may pose risks of covid spread. Should an awareness and knowledge of covid 19 in cholera endemic setting is developed, it is the residents of poor nation that stand to benefit the most.